The Potential Contribution of Fiscal Policy to Rebalancing and Growth in New Zealand - Schule, Werner (IMF Working Papers; Working Paper, 2010)
Simulations with the Fund's GIMF model show that raising government savings in New Zealand permanently by 1 percent of GDP is likely to improve the current account balance by about 1\2 percent of GDP. The way government savings are achieved matters for GDP but little for the current account. However, results are sensitive to changes in the risk premium. Fiscally neutral changes in taxes and expenditures can raise output in the long run.